Effective Treatment of a Melanoma Patient with Hemophagocytic Lymphohistiocytosis after Nivolumab and Ipilimumab Combined Immunotherapy - Pacholczak-Madej, Renata; Grela-Wojewoda, Aleksandra; Lompart, Joanna; Żuchowska-Vogelgesang, Beata; Ziobro, Marek (Prague medical report, 2022)
Immune checkpoint inhibitors have significantly improved the prognosis of melanoma patients. However, these therapies may trigger unexpected immune-related adverse events (irAEs), which are challenging in making the proper diagnosis and providing treatment. Hematological toxicities are possible irAEs, but were poorly evaluated in clinical trials and treatment recommendations of this specific complications are limited. We present a stage IV melanoma patient who developed an extremely rare toxicity - hemophagocytic lymphohistiocytosis (HLH) after the 4th course of combined immunotherapy with nivolumab and ipilimumab. The patient was steroid resistant and only the treatment with various immunosuppressive agents provided control of the disease and finally melanoma regression. In this report, we evaluated the methods of HLH treatment and described our modification of available protocols. Immediate immunosuppression can be life-saving and due to rarity of this condition as well as lack of specific recommendations, every report is valuable for clinicians, especially when treatment was effective.
Keywords: Nivolumab; Ipilimumab; nivolumab; Immune-related adverse events; Humans; lymfohistiocytóza hemofagocytární; lidé; imunoterapie; Immunotherapy; Melanoma; Nivolumab and ipilimumab; Lymphohistiocytosis, Hemophagocytic; ipilimumab; melanom; Hemophagocytic lymphohistiocytosis